Electrospun Resveratrol-Loaded Polyvinylpyrrolidone/Cyclodextrin Nanofibers and Their Biomedical Applications - Ying-Cheng Lin; Stephen Chu-Sung Hu; Pao-Hsien Huang; Tzu-Ching Lin; Feng-Lin Yen (MDPI AG, 2020)
Resveratrol is a naturally occurring polyphenol compound which has been shown to possess antioxidant and anti-inflammatory properties. However, its pharmaceutical applications are limited by its poor water solubility. In this study, we used electrospinning technology to synthesize nanofibers of polyvinylpyrrolidone (PVP) and hydroxypropyl-β-cyclodextrin (HPBCD) loaded with resveratrol. We used X-ray diffractometry to analyze crystalline structure, Fourier transform infrared spectroscopy to determine intermolecular hydrogen bonding, antioxidant assays to measure antioxidant activity, and Franz diffusion cells to evaluate skin penetration. Our results showed that the aqueous solubility of resveratrol nanofibers was greatly improved (by more than 20,000-fold) compared to the pure compound. Analysis of physicochemical properties demonstrated that following nanofiber formation, resveratrol was converted from a crystalline to amorphous structure, and resveratrol formed new intermolecular bonds with PVP and HPBCD. Moreover, resveratrol nanofibers showed good antioxidant activity. In addition, the skin penetration ability of resveratrol in the nanofiber formulation was greater than that of pure resveratrol. Furthermore, resveratrol nanofibers suppressed particulate matter (PM)-induced expression of inflammatory proteins (COX-2 and MMP-9) in HaCaT keratinocytes. Therefore, resveratrol-loaded nanofibers can effectively improve the solubility and physicochemical properties of resveratrol, and may have potential applications as an antioxidant and anti-inflammatory formulation for topical skin application.